Contraceptive choices and satisfaction: a cross-sectional analysis of sociodemographic influences - Maria Åkesson; Jan Brynhildsen; Tanja Tydén; Niklas Envall; Helena Backman; Yvonne Skogsdal (Upsala Journal of Medical Sciences)
Introduction: Investigating factors associated with contraceptive satisfaction is important to create a basis for tailored contraceptive counseling. In this study, we aimed to explore how sociodemographic characteristics affected women’s level of satisfaction and choice of different contraceptive methods, using data collected during a randomized controlled trial (RCT) in the region Örebro County, Sweden. Methods: This cross-sectional study utilized data from a previously conducted RCT. Eligible participants were women aged 20–40 years who sought contraceptive counseling. All women who participated in the RCT and completed a follow-up questionnaire were included in the analysis. Results: Between February 2015 and March 2016, 1,946, participants were enrolled in the trial, with 1,198 (61.6%) completing the 2-month follow-up questionnaire. Overall, 81.3% of women reported being ‘very satisfied’ or ‘satisfied’ with their contraceptive method. Participants aged 27–40 years used long-acting reversible contraception (LARC) to a higher extent compared with those aged 20–26 years (adjusted odds ratio [aOR] 1.92, 95% confidence interval [CI] 1.44–2.56). Older age was associated with lower satisfaction (aOR 0.55, 95% CI 0.33–0.94).Participants with a body mass index (BMI) ≥ 25 more often used LARC (aOR 1.68, 95% CI 1.24–2.28) but were also more likely to report no use of contraceptives at all (aOR 1.56, 95% CI 1.01–2.43) compared with BMI < 25. The level of satisfaction tended to decrease with increasing BMI. Country of birth and educational level were not associated with satisfaction. Conclusions: The use of LARC was more common among women with BMI ≥ 25 and older women. While BMI, education, and place of birth did not affect satisfaction, women aged 27–40 reported lower satisfaction. These findings contrast with prior studies and highlight the complex sociodemographic influences on contraception experiences.